Outcomes are Worse in US Patients Undergoing Surgery on Weekends Compared With Weekdays. Issue 6 (June 2016) - Glance, Laurent G.; Osler, Turner; Li, Yue; Lustik, Stewart J.; Eaton, Michael P.; Dutton, Richard P.; Dick, Andrew W.
Abstract : Background: Increasing surgical access to previously underserved populations in the United States may require a major expansion of the use of operating rooms on weekends to take advantage of unused capacity. Although the so-called weekend effect for surgery has been described in other countries, it is unknown whether US patients undergoing moderate-to-high risk surgery on weekends are more likely to experience worse outcomes than patients undergoing surgery on weekdays. Objective: The aim of this study was to determine whether patients undergoing surgery on weekends are more likely to die or experience a major complication compared with patients undergoing surgery on a weekday. Research Design: Using all-payer data, we conducted a retrospective cohort study of 305, 853 patients undergoing isolated coronary artery bypass graft surgery, colorectal surgery, open repair of abdominal aortic aneurysm, endovascular repair of abdominal aortic aneurysm, and lower extremity revascularization. We compared in-hospital mortality and major complications for weekday versus weekend surgery using multivariable logistic regression analysis. Results: After controlling for patient risk and surgery type, weekend elective surgery [adjusted odds ratio (AOR)=3.18; 95% confidence interval (CI), 2.26–4.49; P <0.001] and weekend urgent surgery (AOR=2.11; 95% CI, 1.68–2.66; P <0.001) were associated with a higher risk of death compared with weekday surgery. Weekend elective (AOR=1.58; 95% CI, 1.29–1.93; P <0.001) and weekend urgent surgery (AOR=1.61; 95% CI, 1.42–1.82; P <0.001) were also associated with a higher risk of major complications compared with weekday surgery. Conclusions: Patients undergoing nonemergent major cardiac and noncardiac surgery on the weekends have a clinically significantly increased risk of death and major complications compared with patients undergoing surgery on weekdays. These findings should prompt decision makers to seek to better understand factors, such physician and nurse staffing, which may contribute to the weekend effect. Abstract : Supplemental Digital Content is available in the text.